Ensino de leitura e escrita através do gênero crônica: uma abordagem sociointeracionista - Alves, Maryngá Meireles Cardoso (2017)
We live in a society in which, more and more, reading and writing have been valued. In this context, the act of reading and writing involves a matter of citizenship as it becomes a form of social inclusion. They enables the social subject to develop his creative competence and his ability to position itself critically on the world in which it is inserted. The entry of the subject in the literate world occurs even before it enters the school environment. However, the school faces the challenge of teaching to read and write. Such confrontation has been undertaken, but not achieving satisfactorily the target goal of forming citizens able to use oral and written language in its communicative interactions. This issue motivated our research whose focus is the teaching of reading and writing through the chronicle genre, from a socio-interactionist perspective. We aim to identify the main difficulties in the textual production process of chronicle genre and intervene, from the didactic sequence, in order to minimize the problems encountered. For this work we are based on Bakhtin's studies (2003) on the discourse genre and on language from a socio-interactionist perspective, as well as Marcuschi (2008), Geraldi (2002), Solé (1998), Koch and Elias (2014), Cavalcante (2013), Antunes (2009) and Dolz et Schneuwly (2004). These researchers conduct studies on the understanding and text production in Portuguese Language teaching, based on the understanding of language as a form of interaction, supporting the objective of developing in the student greater proficiency in oral, reading and writing practices. The corpus of our work is formed by students' textual productions collected through activities that comply the following methodology: application of a questionnaire to verify the class knowledge about the chronicle gender followed by workshops, based on the didactic sequence, in which readings and textual productions of the chronicle genre were carried out. The analysis of the results pointed out that even though they present difficulties in structuring the text to the chronicle genre profile, we verified the students evolution regarding the process of textual production, since a significant part of the students of the 9th grade of Elementary School was able to elaborate text close to the proposed genre.